The factors influencing car use in a cycle-friendly city: the case of Cambridge - Carse, Andrew (Elsevier Ltd, 2013)
Encouraging people out of their cars and into other modes of transport, which has major advantages for health, the environment and urban development, has proved difficult. Greater understanding of the influences that lead people to use the car, particularly for shorter journeys, may help to achieve this. This paper examines the predictors of car use compared with the bicycle to explore how it may be possible to persuade more people to use the bicycle instead of the car. Multivariable logistic regression was used to examine the socio-demographic, transport and health-related correlates of mode choice for work, shopping and leisure trips in Cambridge, a city with high levels of cycling by UK standards. The key findings are that commuting distance and free workplace parking were strongly associated with use of the car for work trips, and car availability and lower levels of education were associated with car use for leisure, shopping and short-distanced commuting trips. The case of Cambridge shows that more policies could be adopted, particularly a reduction in free car parking, to increase cycling and reduce the use of the car, especially over short distances.